Sustained IP3-linked Ca2+ signaling promotes progression of triple negative breast cancer cells by regulating fatty acid metabolism - Filadi, Riccardo; De Mario, Agnese; Audano, Matteo; Romani, Patrizia; Pedretti, Silvia; Cardenas, Cesar; Dupont, Sirio; Mammucari, Cristina; Mitro, Nico; Pizzo, Paola (Frontiers in Cell and Developmental Biology, 2023)
Rewiring of mitochondrial metabolism has been described in different cancers as a key step for their progression. Calcium (Ca2+) signaling regulates mitochondrial function and is known to be altered in several malignancies, including triple negative breast cancer (TNBC). However, whether and how the alterations in Ca2+ signaling contribute to metabolic changes in TNBC has not been elucidated. Here, we found that TNBC cells display frequent, spontaneous inositol 1,4,5-trisphosphate (IP3)-dependent Ca2+ oscillations, which are sensed by mitochondria. By combining genetic, pharmacologic and metabolomics approaches, we associated this pathway with the regulation of fatty acid (FA) metabolism. Moreover, we demonstrated that these signaling routes promote TNBC cell migration in vitro, suggesting they might be explored to identify potential therapeutic targets.